Evaluation of the Peripheral Rim Instability of the Discoid Meniscus in Children by Using Weight-Bearing Magnetic Resonance Imaging. Issue 2 (March 2021) - Jin, Bo; Zhen, Junping; Wei, Xiaochun; Zhou, Yukun; Bian, Wenjin; Yang, Jie; Fan, Zhichang
Abstract : Objective: The aim of the study was to assess the peripheral rim instability and the clinical value of discoid meniscus. Methods: We retrospectively studied 79 magnetic resonance imaging (MRI) examinations of discoid meniscus from May 2017 to September 2019. The patient symptoms and physical findings were documented. The patients underwent "dedicated" 0.25 T supine and weight-bearing MRI examination. Finally, all patients underwent arthroscopy. Results: Sound/clicking during motion ( P = 0.009) and limited extension ( P = 0.044) of subjective symptoms, clunk during motion ( P = 0.035), and flexion contracture ( P = 0.012) of physical findings were significant predictors of peripheral rim instability. The comparison of the weight-bearing MRI with the supine position MRI demonstrated that the disformed discoid meniscus was shifted significantly and that no shift was displaced centrally ( P = 0.001). A correlation between discoid meniscal displacement and the presence of peripheral rim instability in arthroscopy was noted ( P < 0.001) using weight-bearing MRI. Conclusions: The clinical symptoms of the patients combined with weight-bearing MRI can determine peripheral rim instability optimally.